Difference in SWOT Analysis Factors : A Systematic Review - Suprajitno Suprajitno; Imam Zaenuri; Muliyadi Muliyadi (Journal of Ners and Midwifery, 2021)
Introduction: SWOT analysis can be used to assess the position of an organization that has considered internal and external conditions. The objective of this systematic review is to find out the differences in SWOT analysis carried out by health service facilities outside Indonesia and the other country. Method: A systematic review used the PRISMA method. The search keywords used were strategic management, hospitals, health facilities, health services, and SWOT analysis obtained from Google Scholar, Science Direct, ProQuest, and PubMed. The articles analyzed were fully accessible and published in 2010-2020. Result: The main difference of analysis was that in Indonesia illustrates that the SWOT analysis was aimed at hospital organizations and few were oriented towards special services which has similar indicators on internal and external factors. Meanwhile, outside Indonesia, SWOT analysis was directed at specific health services so that it has different internal and external factors of indicator. Discussion: The difference analysis illustrates that the needs of an organization are different in strategic management development.